Updated taxonomic circumscription of Chamaecrista sect. Absus subsect. Absus series Rigidulae (Leguminosae, Caesalpinioideae) - Souza, Alessandro Oliveira De; Da Silva, Marcos José (Phytotaxa, 2020)
Anupdated circumscription and a taxonomic treatment of Chamaecrista sect. Absus subsect. Absus ser. Rigidulae is presented based on the results of previous phylogeny study where the series has emerged as monophyletic with exclusion of two species (C. brachyblepharis and C.ciliolata) and inclusion of two others species (C. botryoides and Ch. sincorana) in its circumscription. This revision resulted from consulting the specialized literature, analyzing of about 1400 collections from national and foreign herbaria. In this new circumscription, the series becomes the largest series of the genus with 32 species endemics to Brazil and distributed mainly in the Brazilian Central Plateau. Two new records in Brazilian states were reported, one to Bahia (Ch. feliciana) and two to Minas Gerais (Ch. benthamiana, Ch. rupestrium); an identification key of the species, morphologic descriptions, notes on taxonomy and geographic distribution of the taxa, conservation status, as well as illustrations and images of diagnostic characters are presented. In addition, the species typification remains updated with all categories indicated first with their respective barcodes.